Emission effects of cooperative adaptive cruise control: A simulation case using sumo - Erdağı, İsmet Gökşad; Silgu, Mehmet Ali; Celikoglu, Hilmi Berk; Silgu, Mehmet Ali (EasyChair, 2019)
The recent advances in adaptive control and autonomous vehicles have given rise to the studies on cooperative control of road vehicles, and the consequent effects on traffic flow performances. In this paper, we summarize our findings from a simulation-based solution of a problem that seeks the joint optimization of a number of link-based performances of vehicular traffic flow considering explicitly the emissions exhausted using the Eclipse SUMO micro-simulation environment in order to discuss the effectiveness of the penetration rates of cooperatively controlled vehicles in mixed traffic. © 2020 Elsevier B.V., All rights reserved.
International Conference on Simulation of Urban Mobility, SUMO 2019 -- Berlin -- 237389
Keywords: [No Keywords]